New Insight into Isoprenoids Biosynthesis Process and Future Prospects for Drug Designing in Plasmodium - Saggu, Gagandeep S.; Pala, Zarna R.; Garg, Shilpi; Saxena, Vishal (Frontiers in Microbiology, 2016)
The MEP (Methyl Erythritol Phosphate) isoprenoids biosynthesis pathway is an attractive drug target to combat malaria, due to its uniqueness and indispensability for the parasite. It is functional in the apicoplast of Plasmodium and its products get transported to the cytoplasm, where they participate in glycoprotein synthesis, electron transport chain, tRNA modification and several other biological processes. Several compounds have been tested against the enzymes involved in this pathway and amongst them Fosmidomycin, targeted against IspC (DXP reductoisomerase) enzyme and MMV008138 targeted against IspD enzyme have shown good anti-malarial activity in parasite cultures. Fosmidomycin is now-a-days prescribed clinically, however, less absorption, shorter half-life, and toxicity at higher doses, limits its use as an anti-malarial. The potential of other enzymes of the pathway as candidate drug targets has also been determined. This review details the various drug molecules tested against these targets with special emphasis to Plasmodium. We corroborate that MEP pathway functional within the apicoplast of Plasmodium is a major drug target, especially during erythrocytic stages. However, the major bottlenecks, bioavailability and toxicity of the new molecules needs to be addressed, before considering any new molecule as a potent antimalarial.